2017
DOI: 10.1016/j.ihj.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric indicators as predictor of pre-diabetes in Indian adolescents

Abstract: IntroductionIn India, there are approximately 41 million diabetics to date. Impaired glucose tolerance or pre-diabetes may occur as early as adolescence.ObjectiveTo find out the cut-off values of body mass index (BMI) and waist circumference to predict pre-diabetes in adolescents in north India.MethodsA cross-sectional study was conducted among 526 students aged 17–19 years, in the Institute of Paramedical Sciences, Chatrapati Shahuji Maharaj University, Kanpur. A pre-tested questionnaire was used and the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…is finding was close to the report from a study done in India, which showed the cut-off point of BMI for predicting prediabetes was 22.8 kg/m 2 in boys and 20.5 kg/m 2 in girls [9]. A study among Japanese showed BMI ≥ 23 is a risk factor for insulin resistance and diabetes [40].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…is finding was close to the report from a study done in India, which showed the cut-off point of BMI for predicting prediabetes was 22.8 kg/m 2 in boys and 20.5 kg/m 2 in girls [9]. A study among Japanese showed BMI ≥ 23 is a risk factor for insulin resistance and diabetes [40].…”
Section: Discussionsupporting
confidence: 88%
“…A population-based cohort study showed that BMI was not a significant risk factor for prediabetes [17]. Another study showed that BMI was a good predictor of prediabetes for both sexes [9]. Among Ethiopian, Malaysian, and ai, body fat percent was reported to be under estimated by BMIbased Caucasian predication equation [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In a study carried out by Pandey et al, on paramedic students of Kanpur region, both boys and girls, aged between 17 and 19 years the prevalence of prediabetes was reported to be 32.1%. 13 Anjana et al, in the phase III of Indian Council of Medical Research-India Diabetes study in the North Eastern states of India from 2012 to 2015 found the incidence of prediabetes from 6% in Mizoram to 14.7% in Tripura. 14 Two large-scale national surveys conducted in China in the year 2007 and 2010 revealed that the prevalence of prediabetes increased from 16.0% to 50.9% in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…18 Yet, a longitudinal study from an ethnically diverse population of US adolescents indicated that although BMIchange was associated with most of the cardiometabolic risk factors, only WC could predict changes in FPG. 45 Cross-sectional studies from different populations have also indicated inconsistent results regarding the preferable adiposity indices which are associated with insulin resistance or prediabetes, some showing stronger associations with BMI, 46,47 and others highlighting WC as a better predictor. 48,49 Our findings indicate that central adiposity does not have any association with IFG, independent of general adiposity.…”
Section: Discussionmentioning
confidence: 99%